(D^3-7DD'^2-6D'^3)z=cos(2x-3y)
"(D^3-7DD'^2-6D'^3)z=cos(2x-3y)"
Auxillary equation is:
"m^3-7m-6=0"
"(m+2)(m+1)(m-3)=0"
"m = -1, -2, 3"
C.F.="f_1(y-x)+f_2(y-2x)+f_3(y+3x)"
P.I. "=\\frac 1 {D^3-7DD'^2-6D'^3}cos(2x-3y)"
Put "D^2 = -4, D'^2 = -9"
P.I. "= \\frac 1 {-4D+63D+54D'}cos(2x-3y) =" "\\frac 1 {59D+54D'}cos(2x-3y)"
"=\\frac {59D-54D'} {3481D^2-2916D'^2}cos(2x-3y)" "= \\frac {59D-54D'} {=13924+26244}cos(2x-3y)"
"=\\frac 1 {12320}(59Dcos(2x-3y)-54D'cos(2x-3y))"
"=\\frac 1 {12320}(-118sin(2x-3y)-162sin(2x-3y))"
"=-\\frac {280}{12320}sin(2x-3y)=-\\frac{7}{176}sin(2x-3y)"
The complete solution "z=" C.F.+P.I."=f_1(y-x)+f_2(y-2x)+f_3(y+3x)" "-\\frac{7}{176}sin(2x-3y)"
Answer: "z=f_1(y-x)+f_2(y-2x)+f_3(y+3x)-\\frac{7}{176}sin(2x-3y)"
Comments
Leave a comment